Ink Painting of Orchids among the Literati in the Qing and Choson Dynasties - Herin Jung (Journal of Global Initiatives, 2011)
Genres of cultural products have flowed in and out between China and Korea for thousands of years. It is well known that among these genres, the orchid was one of the most elegant subjects in ink painting. Although research has shown which types and how many works have been exchanged between the two countries, the ideas beneath the works deserve greater attention. The works of Kim Chong-hui (1786-1856) in the late Choson Dynasty are particularly valuable. Well known as a great calligrapher and erudite scholar, Kim profoundly explored art history and theory and was especially knowledgeable about successive painters of traditional orchid paintings, from Zheng Suonan to Zheng Xie. Though he was most interested in Zheng Xie's works, Kim only selectively applied Zheng's ideas because of his strongly kept traditional literati morals, including an adherence to the strict morals of zhongyong, the Doctrine of the Mean. Another master in ink painting of orchids in the Choson Dynasty was Cho Hui-ryong (1789-1866) who, although a member of the literati, did not belong to the scholar-official class. Cho resisted the traditional values of scholarship on literati paintings for more individual and worldly values, intending to follow Zheng's ideas but altering them instead. Kim and Cho seem to have admired different aspects of Zheng's ideas on orchid painting.